Test Design and Minimum Standards - DeMarzo, Peter M.; Kremer, Ilan; Skrzypacz, Andrzej (American Economic Review, 2019)
We analyze test design and certification standards when an uninformed seller has the option to generate and disclose costly information regarding asset quality. We characterize equilibria by a minimum principle: the test and disclosure policy are chosen to minimize the asset’s value conditional on nondisclosure. Thus, when sellers choose the information provided, simple pass/fail certification tests are likely to dominate the market. A social planner could raise informational and allocative efficiency, and lower deadweight testing costs, by raising the certification standard. Monopolist certifiers also satisfy the minimum principle but set a higher standard and reduce testing rates to maximize revenue. (JEL D42, D83, L12, L15)